Influence of Incorporating PVC Waste on the Mechanical Properties of Cement Mortar - Altwair, Nurdeen; Elghwaria, Heba (Journal of Pure & Applied Sciences, 2023)
Currently, recycling of industrial wastes to reduce the environmental impact is the major concerns of researchers. Polyvinyl chloride (PVC) is one of the  waste materials worldwide, with considerable impacts on environmental. Recycling PVC wastes in the concrete or mortar industry is one of the adopted ways to decrease such impact. The purpose of this paper is the reuse of PVC waste deriving from the workshops manufactured doors and windows which made of PVC material. The waste of polyvinyl chloride was collected from one of the factories located in AL-Khoms, then the waste was sieved, the sample that passed through Sieve No.4  and  retained on sieve No.10 was taken. The PVC waste  proportions of (0.06 ˛ 0.08 ˛ 0.1) by weight of cement was added to the mix mortar. The tests carried out during this study were; air content of fresh cement mortar, flow table, dry density of hardened cement mortar, flexural and compression, free shrinkage and finally ultrasound pulse velocity. The results obtained showed a significant improvement in the sound insulation and a decrease in the dry density of the mortar. While the compressive and flexural strength results were slightly lower compared to the standard mortar. In addition, a decrease in the values of flow, free shrinkage and air content was observed with an increase in the PVC content. Nevertheless, the mortar obtained contributes to the conservation of natural resources and maintains the mechanical properties of the cement mortar in structural applications.